Development of Augmented Reality Technology in Tourism as an Effort to Preserve Local Culture - Listra Frigia Missianes Horhoruw; Noviyanti P; Yuliana Yuliana; Mira Mira; Jones Parlindungan Nadapdap (Jurnal Info Sains : Informatika dan Sains, 2023)
This research examines the development of Augmented Reality (AR) technology in the context of tourism with a focus on the MAKAR application. Involving literature review, cultural sustainability analysis, AR development, and field trials, this study aims to elucidate the potential of AR in preserving local cultural sustainability while enhancing the tourist experience. The literature review provides a profound understanding of AR applications in the tourism sector, highlighting key concepts and their implications. Cultural sustainability analysis lays the ethical foundation for AR development that respects and strengthens local cultural heritage. The AR development process is carried out through the selection of the MAKAR platform, combining technological innovation with local wisdom. This stage involves choosing technologies that support technical requirements while considering positive impacts on cultural sustainability and local community participation. Field trials involve five different tourist locations using various types of smartphones. The results provide insights into user responses, cultural sustainability impacts, and application adaptability to different devices. Despite some delays, overall, the MAKAR application successfully delivers a captivating tourist experience. This research concludes that AR development through the MAKAR application has significant potential in preserving cultural sustainability while providing an innovative tourist experience.